Pengaruh Inflasi, Tingkat Suku Bunga BI, Kurs Rupiah, dan Pertumbuhan Produk Domestik Bruto (PDB) terhadap Indeks Harga Saham Gabungan Sektor Konsumsi Periode Tahun 2012-2014 - Marpaung, Megayanti; Rustiyaningsih, Sri; Purbandari, Theresia (JRMA | Jurnal Riset Manajemen dan Akuntansi, 2017)
Composite Stock Price Index (CSPI) that listed on the Indonesia Stock Exchange (BEI) has always been a benchmark for investors to make investment decisions. Rise and fall of JCI influenced by several factors occurring in a country. This study aimed to examine the effect of inflation, BI rate, the rupiah exchange rate against the U.S dollar, and the growth of gross domestic product (GDP) of the composite stock price index consumer sector. The population in this study are the stock price index consumer sector for the period 2012-2014. The sample in this study is the entire population in the study. The sampling technique using saturated sample / census. The analysis technique used multiple linear regression. The results of this study show the BI rate has negative effect to the stock price index consumer sector, the rupiah exchange rate has negative effect but not significant, and the inflation as well as the growth in gross domestic product (GDP) does not affect to the stock price index consumer sector.